Hyperoside alleviates myocardial ischemia-reperfusion injury in heart transplantation by promoting mitochondrial fusion via activating the Stat3-Tom70-Opa1 pathway - Hou, Jincheng; Lan, Hongwen; Li, Chenghao; Wang, Zihao; Zheng, Qiang; Wang, Kan; Xiong, Tixiusi; Wang, Yixuan; Shi, Jiawei; Dong, Nianguo (Frontiers in Pharmacology, 2025)
BackgroundMyocardial ischemia–reperfusion injury (IRI) is the major cause of primary graft dysfunction in heart transplantation, which is characterized by mitochondrial dysfunction. Hyperoside is a bioactive compound that has been reported to have pharmacological potential for cardiac and mitochondrial protection. Here, we investigated the protective effect of hyperoside during myocardial IRI and identified the underlying mechanisms.MethodsIn this study, we established IRI in an in vivo murine heterotopic heart transplantation model and an in vitro hypoxia–reoxygenation cell model. Inflammatory responses, oxidative stress level, mitochondrial function, and cardiomyocyte apoptosis were evaluated.ResultsWe found that hyperoside pretreatment alleviated through reducing MDA content, LDH activity, TUNEL positive cells, serum cTnI level, Bax protein expression and the level of inflammatory cytokines, and increasing SOD activity and Bcl-2 protein expression. Furthermore, hyperoside pretreatment improved Opa1-mediated mitochondrial fusion, upregulated mitochondrial ATP content and downregulated NADP+/NADPH and GSSG/GSH ratios. Opa1 inhibitor blunted the protective effects of hyperoside. Mechanistically, Co-immunoprecipitation experiments showed the binding property between Tom70 and Opa1, siRNA knockdown, AAV-mediated loss-of-function and gain-of-function approaches suggested that hyperoside-promoted Opa1-mediated mitochondrial fusion required the upregulation of Tom70.ConclusionCollectively, we demonstrated for the first time that hyperoside administration alleviates myocardial IRI by promoting Opa1-mediated mitochondrial fusion in vivo and in vitro. The Tom70-Opa1 pathway was essential for cardioprotective effects of hyperoside treatment. The results in our study indicated that hyperoside or promotion of mitochondrial fusion might be a new potential option for the prevention and treatment of IRI in heart transplantation.